Unlocking the bone: Fcγ-receptors and antibody glycosylation are keys to connecting bone homeostasis to humoral immunity. - Seeling, Michaela; Nimmerjahn, Falk (Annals of Translational Medicine, 2015)
Bone tissue is characterized by a constant remodeling process mediated by bone resorbing osteoclasts and bone forming osteoblasts. During autoantibody mediated autoimmune diseases, such as inflammatory arthritis, this balance is disturbed and the de novo generation of osteoclasts through cross-linking of activating Fcγ-receptors (FcγRs) expressed on osteoclasts results in excessive bone erosions and joint destruction. A recent study by Negishi-Koga and colleagues now provides conclusive evidence, that FcγRs may also play a crucial role for bone homeostasis during the steady state, further highlighting the tight interactions between the bone and immune system.